Pudendal Nerve Block in the Greater Sciatic Foramen A New Technique for Transurethral Surgery. Issue 3 (July 1987) - Silverman, David G.; Chen, Linda; Gray, Dennis C.; Wein, Alan J.; Harty, Michael; Smith, Theodore C.
Abstract : Although previously it appeared that multiple needle sticks would be required to anesthetize the somatic and visceral pathways that transmit pain during transurethral surgery, the authors' experience indicates that this may be accomplished with a single injection bilaterally. Injection near the pudendal nerve, as it courses through the greater sciatic foramen, can provide anesthesia of the glans penis, urethra, prostate, and bladder. Block of the pudendal nerve in the greater sciatic foramen is herein described as a new regional anesthetic technique for surgical procedures of the lower genitourinary tract. After routine premedication, bilateral block provided adequate anesthesia for 15 of 30 male patients who had transurethral surgery. Supplementation with dorsal nerve block and intravenous fentanyl (50-150 μg) resulted in adequate conditions in 11 of the remaining 15 patients. The technique may be a valuable alternative in certain settings; however, it does not offer the speed and reliability of major conduction anesthesia.